2019
DOI: 10.3390/ani9090610
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Oral UMP/UR Administration Regulates Lipid Metabolism in Early-Weaned Piglets

Abstract: Simple SummaryUridine monophosphate (UMP) and uridine (UR) are rich in sow’s milk. The results from this study showed that UMP and UR affect the lipid profile and lipid metabolism in weanling piglets. It is suggested that UMP and UR improve the energy status in early-weaned piglets.AbstractAs a main ingredient of milk, the nucleotides content is about 12–58 mg/g, which plays a critical role in maintaining cellular function and lipid metabolism. This study was conducted to evaluate the effects of short-term uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Uridine catabolism can also lead to an increase in cellular acetyl-CoA pool, which in turn increases protein acetylation [10]. Our previous studies showed that oral administration of uridine stimulated intestinal development, promoted nucleotide transport, improved growth performance, and regulated the fatty acid composition and lipid metabolism in weaned piglets [41][42][43][44]. We have demonstrated that maternal dietary supplement UR contributed to reducing the occurrence of diarrhea by regulating cytokine secretion and intestinal mucosal barrier function of suckling pigs [45].…”
Section: Relationships Among Uridine and Glucose Lipid And Amino Acmentioning
confidence: 96%
“…Uridine catabolism can also lead to an increase in cellular acetyl-CoA pool, which in turn increases protein acetylation [10]. Our previous studies showed that oral administration of uridine stimulated intestinal development, promoted nucleotide transport, improved growth performance, and regulated the fatty acid composition and lipid metabolism in weaned piglets [41][42][43][44]. We have demonstrated that maternal dietary supplement UR contributed to reducing the occurrence of diarrhea by regulating cytokine secretion and intestinal mucosal barrier function of suckling pigs [45].…”
Section: Relationships Among Uridine and Glucose Lipid And Amino Acmentioning
confidence: 96%
“…In addition, as a nuclear receptor, PPAR regulates placental development and lipid metabolism (51,52) . Our previous study in early-weaned piglets showed that short-term UR treatment might regulate protein expression of mTOR and AKT pathways (16) . Similarly, we found that UR treatment could improve the phosphorylation of mTOR and AKT, raptor, which indicated that UR may regulate placental transfer through mTORC1 and AKT pathway.…”
Section: Maternal Supplementation With Uridine-regulated Protein Exprmentioning
confidence: 99%
“…UR also plays an important role in regulating energy homoeostasis and bile acid metabolism via regulating lipid metabolism (11) . Short-term UR treatment to early-weaned piglets might stimulate de novo lipid synthesis via the AKT pathways (16) , it also affected cholesterol and bile acid metabolism of mice (17) and the diurnal variations of lipid metabolism in the liver of mice can be regulated by UR (18) . Thus, UR plays an important role in the metabolism of amino acids and fatty acids in the sows.…”
mentioning
confidence: 99%
“…Uridine (UR) comprises one of the nucleotides, and dietary supplementation with UR modulates lipid and AA metabolism in mice or sows 8–10 . Most interestingly, short‐term oral UR 5'‐monophosphate (5'‐UMP) or UR to piglets could improve energy utilization by modifying lipid metabolism 11 . Thus, nucleotides play an important role in regulating the body's amino acid and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%